V ně - Šrubařová, Zuzana (Vysoké učení technické v Brně. Fakulta výtvarných umění, 2025)
Ve své diplomové práci se zabývám tématem komfortu, který pro mě paradoxně vychází z konfrontace s vnitřním neklidem. Toto téma mě provází napříč celým studiem a postupně jsem se v rámci své tvorby posunula od čistě osobní vizualizace těchto pocitů k jejich sdílení s ostatními. V centru mého zájmu nejsou konkrétní prožitky nebo myšlenky, ale spíše to, jak se s vnitřními nepokoji vypořádávají mí blízcí – ať už vědomě, nebo nevědomě. Právě tato různorodost přístupů a reakcí se stala východiskem pro vznik prostorové instalace, která vizuálně zpracovává tyto procesy. Nedílnou součástí instalace je i zvukový záznam rozhovorů, které tematiku otevírají z různých úhlů pohledu a pomáhají dotvářet atmosféru celého díla. Skrze tuto práci reflektuji jemné, často podvědomé vrstvy zkušeností, jejichž kořeny sahají až do dětských vzpomínek.

In my diploma thesis, I explore the notion of comfort, which for me paradoxically emerges through a confrontation with inner unrest. This theme has been a consistent thread throughout my academic journey, during which I have gradually transitioned from a purely personal visualization of these emotional states toward their externalization and shared exploration through my artistic practice. Rather than focusing on specific experiences or individual thoughts, my attention is directed toward the ways in which those close to me process inner unrest—whether consciously or unconsciously. This diversity of internal responses formed the conceptual basis for the creation of a spatial installation, which seeks to translate these intangible processes into a visual and spatial language. A key component of the installation is an audio recording of conversations that open the theme to multiple perspectives and contribute to the immersive atmosphere of the work. Through this project, I reflect on the subtle, often subconscious dimensions of human experience, the origins of which can be traced back to early memories from childhood.
In them
Keywords: vědomí; nevědomí; dětství; vzpomínky; multimediální instalace; komfort; diskomfort; hledání; sdílení; rozhovor; zvukový záznam; consciousness; unconsciousness; childhood; memories; multimedia installation; comfort; discomfort; search; sharing; interview; audio recording